Firefly Algorithm Optimization of Manipulator Robotic Control Based on Fast Terminal Sliding Mode - Mallem, Ali; Douak, Fouzi; Walid, Beneziza; Asma, Bounouara (Journal of Automation, Mobile Robotics and Intelligent Systems, 2023)
In this paper a new algorithm of optimization in the field of manipulator robotic control is presented. The proposed control approach based on fast terminal sliding mode control (FTSMC) in order to guarantee the convergence of the position articulations errors to zero in finite time without chattering phenomena, and the firefly algorithm in order to generate the optimal parameters that ensure minimum reaching time and mean square error and achieve better performances, whose ensure the asymptotic stability of the system using a Lyapunov candidate in presence of disturbances. The simulations are applied on a two-link robotic manipulator with different tracking references by using Matlab/ Simulink , results show the efficiency and confirm the robustness of the proposed control strategy.